Argininamide-type neuropeptide Y Y1 receptor antagonists: the nature of Nω-carbamoyl substituents determines Y1R binding mode and affinity. Issue 2 (20th January 2020) - Buschmann, Jonas; Seiler, Theresa; Bernhardt, Günther; Keller, Max; Wifling, David
Abstract : Replacement of the carbamoyl residue ( R ) in reference compound 2 by larger residues ( e.g. 72 ) strongly affected Y1 R affinity. In case of very bulky carbamoyl substituents ( e.g. 78 ), an inverted binding mode was suggested by induced-fit docking. Abstract : The recently resolved crystal structure of the neuropeptide Y Y1 receptor (Y1 R), co-crystallized with the high-affinity (p K i : 10.11), argininamide-type Y1 R antagonist UR-MK299 (2 ), revealed that the N ω -carbamoyl substituent (van der Waals volume: 139 Å 3 ) is deeply buried in the receptor, occupying a hydrophobic pocket. We synthesized and characterized a series of argininamides, structurally related to 2 . Y1 R affinity decreased with increasing size of the carbamoyl residue (minimal p K i : 5.67). Exceeding a critical size of the substituent (van der Waals volume: 212 Å 3 ), the ligands bound in an inverted mode with the carbamoyl side chain located at the surface of the receptor, as suggested by induced-fit docking and MD simulations.